2006
DOI: 10.7205/milmed.171.7.598
|View full text |Cite
|
Sign up to set email alerts
|

Missed Injuries in Military Patients with Major Trauma: Original Study

Abstract: Missed injuries could usually be encountered in the most seriously injured patients, particularly in those with altered levels of consciousness. Missed injuries were mostly avoidable and most were the result of inadequate clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 0 publications
5
35
1
1
Order By: Relevance
“…Another reason might be that they did not take possession of the trauma victim; they even sometimes think the EMR consulted them unnecessarily, and their prejudice is reflected in their notes. Previous studies have shown that most missed diagnoses were located in the extremities and were musculoskeletal injuries [4,8,11,13]. Missed diagnoses relating to the extremities and the musculoskeletal system were also significantly higher in number in our study (Table 3).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Another reason might be that they did not take possession of the trauma victim; they even sometimes think the EMR consulted them unnecessarily, and their prejudice is reflected in their notes. Previous studies have shown that most missed diagnoses were located in the extremities and were musculoskeletal injuries [4,8,11,13]. Missed diagnoses relating to the extremities and the musculoskeletal system were also significantly higher in number in our study (Table 3).…”
Section: Discussionsupporting
confidence: 59%
“…The objective of this study was to explore a problem that has not been studied previously in a civil hospital in Turkey. Our rate of missed diagnosis (13.3%) was acceptable compared with rates reported in other studies (4.8-22%) performed in various countries [4,8,11,13]. Notwithstanding, it is clearly evident that we have a very high rate of missed injury in this population.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations